The Gale encyclopedia of genetic disorders - Blachford, Stacey (Detroit, MI : Gale Group, 2001)
Presents nearly four hundred articles describing genetic disorders, conditions, tests, and treatments, including high-profile diseases such as Alzheimer's, breast cancer, and heart disease
v.1. A - L -- v.2. M - Z, appendix, glossary, index
Includes bibliographical references and index
Keywords: Genetic disorders -- encyclopedias; Diseases -- encyclopedias